2007
DOI: 10.1080/02652040701644752
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of tiny biodegradable capsules using electrocapillary emulsification

Abstract: Conditions for preparing tiny biodegradable capsules were examined using electrocapillary emulsification that allows one to prepare monodisperse emulsions with ease by applying a DC potential between oil and water phases without mechanical agitation. The results obtained showed that a 1 : 4 mixture of polysorbate 80 (TO-10), a hydrophilic non-ionic surfactant, and sorbitan monooleate (SO-10), an oleophilic surfactant, is appropriate as the surfactant to be added to oil phase, cyclohexane is acceptable as the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…W/O emulsions were prepared with the laboratory-made apparatus for electrocapillary emulsification [7,8]. Briefly, the apparatus consists of the emulsification part, the applied electric potential and liquid dropping rate controlling part, a CCD camera and a monitor.…”
Section: Preparation Of Polyurea Capsulesmentioning
confidence: 99%
“…W/O emulsions were prepared with the laboratory-made apparatus for electrocapillary emulsification [7,8]. Briefly, the apparatus consists of the emulsification part, the applied electric potential and liquid dropping rate controlling part, a CCD camera and a monitor.…”
Section: Preparation Of Polyurea Capsulesmentioning
confidence: 99%
“…Furthermore, decreasing the particle size in the dispersed water phase is necessary. Much pharmaceutical technical information about adjusting the size of particles is now available: for example, rotating membrane emulsification [1,2], shirasu porous glass membrane emulsification [3,4], electrocapillary emulsification [5,6]. These methods adjust particle size on the basis of membrane pore size and shearing force, which depends on the flow of dispersion medium or on contact-surface dielectric constant differences between the dispersion medium and the dispersion phase.…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic atomization is a technique for the atomization of liquid with an electrohydrodynamic (EHD) force, and many studies are reported in recent years . The electrostatic atomization could be classified into three systems as follows: (1) a liquid dispersion into a gas (L/G) system, (2) gas dispersion into a liquid (G/L) system, and (3) a liquid dispersion into a liquid (L/L) system.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, although electrostatic emulsification has potential ability to prepare a uniform nano‐size droplet, reports on the production of drug carrier are few. Some attempts for the drug carrier production were conducted by Abe et al , such as the nano‐capsule of alginate/polylysine complex, which has sizes ranging from 100–500 nm, the Poly(2‐ethylcyanoacrylate), which has sizes ranging from 100–300 nm, and the poly‐urea capsule of around 200 nm …”
Section: Introductionmentioning
confidence: 99%